Prognostic impact of pathological response to neoadjuvant chemotherapy followed by definitive surgery in sinonasal squamous cell carcinoma. (2nd March 2016) - Hirakawa, Hitoshi; Hanai, Nobuhiro; Ozawa, Taijiro; Suzuki, Hidenori; Nishikawa, Daisuke; Matayoshi, Sen; Suzuki, Mikio; Hasegawa, Yasuhisa
Abstract: Background: The significance of neoadjuvant chemotherapy followed by definitive surgery for sinonasal squamous cell carcinoma (SCC) was investigated using surgical specimens. Methods: Surgery was performed in 58 patients, including 43 patients who had received neoadjuvant chemotherapy. The pathological response was classified as grades 0 (no effect), 1 (slight effect), 2 (moderate effect), and 3 (marked effect), and its correlation with prognosis was investigated. Results: Grade 2 or 3 response was observed in 34.9% of cases that received neoadjuvant chemotherapy. Overall survival (OS), disease‐free survival (DFS), locoregional control, and freedom from distant metastasis were significantly better in the effective neoadjuvant chemotherapy group (grades 2 and 3) than in the less effective neoadjuvant chemotherapy group (grades 0 and 1) and the non‐neoadjuvant chemotherapy group combined. Conclusion: Pathological response to neoadjuvant chemotherapy in sinonasal SCC was related to disease prognosis. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E1305–E1311, 2016